Evaluation of Self-Employment Development Factors: Latvian Case - Remeikiene, Rita (Economics and Business, 2015)
The factors that have the impact on selfemployment development have been identified and ranked by importance applying method of expert evaluation. Selfemployment start-up is promoted by the increasing demand in foreign markets, export and lack of competences for all activities while the main barriers are unfavourable economics and institutional environment.